2004
DOI: 10.1177/088840640402700408
|View full text |Cite
|
Sign up to set email alerts
|

Preparing Preservice Teachers to Implement Class Wide Peer Tutoring

Abstract: This study focused on preservice general education teachers who were prepared to use an evidence-based teaching practice and the effects the practice had on their pupils' academic performance. Participants learned to use Juniper Gardens Children's Project's Class Wide Peer Tutoring (CWPT) program through a two-hour workshop and with in class assistance. The amount of time required for each preservice teacher to reach a pre-established training criterion (i.e., unassisted use of CWPT for three consecutive sessi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 17 publications
2
15
0
Order By: Relevance
“…The total time for all training activities was approximately 4 hr. In relation to total training time, this study is more consistent with the results found by Maheady, Harper, Mallette, and Karnes (2004) and , which showed high levels of accuracy in teaching procedures (i.e., 85% or higher) with approximately 4 hr of inservice and coaching. In this study, teachers may have needed little coaching given their previous experience teaching DI programs.…”
Section: Discussionsupporting
confidence: 90%
“…The total time for all training activities was approximately 4 hr. In relation to total training time, this study is more consistent with the results found by Maheady, Harper, Mallette, and Karnes (2004) and , which showed high levels of accuracy in teaching procedures (i.e., 85% or higher) with approximately 4 hr of inservice and coaching. In this study, teachers may have needed little coaching given their previous experience teaching DI programs.…”
Section: Discussionsupporting
confidence: 90%
“…Because we did not reach high levels of fidelity with the nonscripted condition, we don't know how much more or what type of professional development might work. At least four studies have demonstrated that teachers acquire new instructional procedures with higher accuracy when they receive individual follow-up coaching after the initial inservice (Kohler et al, 2001;Kohler, Ezell, & Paluselli, 1999;Kretlow, Wood, & Cooke, 2009;Maheady, Harper, Mallette, & Karnes, 2004;Morgan, Menlove, Salzburg, & Hudson, 1994). Results of these studies suggest a combination of inservice and follow-up coaching might have been more successful in helping the paraeducators reach higher fidelity with the nonscripted version.…”
Section: Limitations Of the Study And Suggestions For Future Researchmentioning
confidence: 99%
“…Similar findings are also cited in the literature. For example, Maheady, Harper, Mallette and Karnes (2004) found that approximately 4 hours of in service training and coaching contributed significantly to the instructional process. The four sessions that Kretlow, Cooke ve Wood (2012) held (one in-service group session, one preliminary interview, one coaching session and one feedback session) lasted approximately four hours.…”
Section: Discussionmentioning
confidence: 99%